Dismissal : a guide to effective management procedures - Roberts, Deryck (Cassell, 1999)
"This practical book covers all the issues involved in hiring and firing staff - from the contract of employment to dismissal. It concentrates on the process of a claim to the Employment Tribunal for unfair dismissal, and looks at contracts of employment, counselling, discipline handling and model disciplinary procedures."--BOOK JACKET.